Stabilizing lithium metal using ionic liquids for long-lived batteries - Basile, A. (Nat Commun, 2016)
Suppressing dendrite formation at lithium metal anodes during cycling is critical for the implementation of future lithium metal-based battery technology. Here we report that it can be achieved via the facile process of immersing the electrodes in ionic liquid electrolytes for a period of time before battery assembly. This creates a durable and lithium ion-permeable solid–electrolyte interphase that allows safe charge–discharge cycling of commercially applicable Li|electrolyte|LiFePO(4) batteries for 1,000 cycles with Coulombic efficiencies >99.5%. The tailored solid–electrolyte interphase is prepared using a variety of electrolytes based on the N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide room temperature ionic liquid containing lithium salts. The formation is both time- and lithium salt-dependant, showing dynamic morphology changes, which when optimized prevent dendrite formation and consumption of electrolyte during cycling. This work illustrates that a simple, effective and industrially applicable lithium metal pretreatment process results in a commercially viable cycle life for a lithium metal battery.